Industrial Relations and the Wage Differentials between Skilled and Unskilled Blue-Collar Workers within Establishments: An Empirical Analysis with Data of Manufacturing Firms - Olaf Hübler; Wolfgang Meyer (Institute for the Study of Labor (IZA), 2000)
Increased wage inequality between skilled and unskilled workers is a stylized fact, which can be observed in many developed countries. Among the explanations advanced for this phenomenon is the increasing globalization, a skill-biased technical progress, restructuring of the firms, and last but not least, a decreasing importance of industrial relations institutions. In the paper, we investigate in a three-step procedure with firms? data whether the latter determinant is influential. We control for the other relevant explanations and split industrial relations into three components - coverage of collective bargaining, existence of a works council, and union density – within a four-equation model. We find an insignificant influence of the union density. A Works council compresses the wage differentials between skilled and unskilled blue-collar workers while coverage is effective in the opposite direction. The latter two effects nearly offset each other.
Keywords: J51; J31; 330; Wage differentials; skilled and unskilled labour; union density; works councils; coverage of collective bargaining; Lohnstruktur; Qualifikation; Facharbeiter; Ungelernte Arbeitskräfte; Arbeitsbeziehungen; Tarifpolitik; Betriebsrat; Gewerkschaftlicher Organisationsgrad; Schätzung; Deutschland